2017
DOI: 10.1111/epi.13891
|View full text |Cite
|
Sign up to set email alerts
|

Vascular, inflammatory, and metabolic factors associated with cognition in aging persons with chronic epilepsy

Abstract: We examined cognition in aging persons with chronic epilepsy; characterized targeted vascular, inflammatory, and metabolic risk factors associated with abnormal cognitive aging in the general population; and examined associations between cognition and vascular, inflammatory, and metabolic health. Participants included 40 persons with chronic localization-related epilepsy and 152 controls, aged 54.6 and 55.3, respectively. Participants underwent neuropsychological assessment, clinical examination, and fasting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Mitochondria have critical cellular functions that influence neuronal excitability including production of adenosine triphosphate, fatty acid oxidation, control of apoptosis and necrosis, regulation of amino acid cycling, neurotransmitter biosynthesis, and regulation of cytosolic Ca(2+) homeostasis. Vascular, inflammatory and metabolic factors can be also implicated in the aging process and can explain cognitive dysfunction in people with epilepsy [13]. All these mechanisms make it difficult to understand whether the association between epilepsy and aging is direct or mediated by other clinical conditions sharing with epilepsy common pathophysiologic abnormalities.…”
Section: Mechanisms Underlying Aging and Epilepsymentioning
confidence: 99%
“…Mitochondria have critical cellular functions that influence neuronal excitability including production of adenosine triphosphate, fatty acid oxidation, control of apoptosis and necrosis, regulation of amino acid cycling, neurotransmitter biosynthesis, and regulation of cytosolic Ca(2+) homeostasis. Vascular, inflammatory and metabolic factors can be also implicated in the aging process and can explain cognitive dysfunction in people with epilepsy [13]. All these mechanisms make it difficult to understand whether the association between epilepsy and aging is direct or mediated by other clinical conditions sharing with epilepsy common pathophysiologic abnormalities.…”
Section: Mechanisms Underlying Aging and Epilepsymentioning
confidence: 99%
“…Receptors for insulin are distributed widely in brain, and via these receptors, insulin modulates synaptic plasticity by regulating the release, uptake, and degradation of neurotransmitters [67,68]. Evident IR occurs in patients with chronic epilepsy [69,70], while in patients with type 1 diabetes mellitus who lack insulin, the risk of epilepsy is 3-fold that in normal controls [71]. And the H1085H C [ T polymorphism of the insulin receptor gene is associated with drug resistance in refractory epilepsy patients [72].…”
Section: The Role and Mechanism Of Zag In Cns Diseasesmentioning
confidence: 99%
“…Population-based studies in patients with epilepsy have found elevated vascular risks [3][4][5] [i.e., hyperlipemia, body mass index (BMI)] and poor health behaviors [2,6] (e.g., decreased physical activity, poor social and occupational functioning) that may place them at greater risk for cognitive impairment. An emerging literature in epilepsy has begun to identify CVRFs associated with cognitive impairment [7][8][9][10]. Recent studies have found abnormalities in vascular, inflammatory, and metabolic biomarkers in patients with epilepsy that are associated with poorer performance on neuropsychological measures of memory, psychomotor speed, attention, language, and working memory [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…An emerging literature in epilepsy has begun to identify CVRFs associated with cognitive impairment [7][8][9][10]. Recent studies have found abnormalities in vascular, inflammatory, and metabolic biomarkers in patients with epilepsy that are associated with poorer performance on neuropsychological measures of memory, psychomotor speed, attention, language, and working memory [8,9]. Furthermore, in the general population, elevated health-related risk factors have been linked to reduced hippocampal volume and memory impairments [11].…”
Section: Introductionmentioning
confidence: 99%